Influence of perceived value of rural labour in China on the labourers’ willingness to return to their hometown: the moderating effect of social support - Zhaoxin Zhang; Lei Wang (International Journal of Agricultural Sustainability)
China is vigorously implementing rural revitalization strategy, emphasizing the significance of human resources in the sustainable development of rural areas and agriculture. As China’s economy is entering a new normal stage, the growth rate of rural labourers’ income in cities is slowing down, and the gap between urban and rural net incomes is gradually closing. The labourers who have migrated are gradually showing the willingness to return to their hometowns for development. This study constructs a theoretical framework for the studying of rural labourers’ willingness to return to their hometowns. It finds that the perceived value of rural labour positively influences their willingness to return. Further perceived extrinsic–intrinsic benefits, perceived extrinsic costs, and their perceived values are all significantly and positively correlated. Moreover, formal support has a positive moderating effect between the perceived value of rural labour and willingness to return. The perceived value of rural labour increases with higher perceived benefits and lower perceived costs; the stronger the perceived benefits and perceived value of labour, the greater the willingness to return.